GRASSHOPPER OPTIMIZATION APPROACH FOR POWER SYSTEM STABILIZERS PATTERN - E. S. Ali; S. M. Abd Elazim (Yanbu Journal of Engineering and Science, 2019)
In this cover, a new meta-heuristic approach called Grasshopper Optimization Approach (GOA) for Power System Stabilizer (PSS) pattern problem is inspected. The parameters of PSSs are perfected by GOA to belittle the time domain objective function. The showing of the organized GOA based PSSs (GOAPSS) has been competed with Differential Evolution (DE) based PSSs (DEPSS) and the Particle Swarm Optimization (PSO) based PSSs (PSOPSS) under varied burden events. The results of the decided GOAPSS are affirmed via damping ratio, eigenvalues, performance indices, and time domain analysis. In addition, the strength of the GOA in earning generous damping characteristics is belayed.